CNF / SA dual rheological regulation and in-situ ion cross-linking reinforced MXene-based fibrous electrode and preparation method and application thereof
Patent Information
- Application Number
- CN202611387374.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-16
AI Technical Summary
然而,这种化学交联方法存在以下缺陷:工艺繁琐,增加了后处理时间,不利于连续化工业生产;外加的金属阳离子会大量残留在纤维网络中,形成电化学惰性物质,不仅增加电极死质量,还可能阻碍电解液离子的快速迁移,导致比容量缩水
[0025] (1) This invention does not use the traditional method of adding metal ions for immersion crosslinking. Instead, it uses an acidic coagulation bath containing chitosan as a crosslinking agent. The amino group of chitosan and the carboxyl group of the spinning solution form an interfacial complex, which not only simplifies the preparation process, but also avoids interference from external metal ions, thus ensuring the purity and electrochemical properties of the fiber network.
Smart Images

Figure CN122930737A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of flexible energy storage materials and micro supercapacitors, specifically relating to a method for preparing CNF / SA dual rheological regulation and in-situ ion crosslinking enhanced MXene-based fibrous electrodes and their application in wearable fibrous supercapacitors. Background Technology
[0002] With the rapid development of wearable smart electronics and flexible devices, one-dimensional fiber-like supercapacitors have become a research hotspot due to their flexibility, ease of weaving, high integration, and safety and stability. MXene (Ti3C2T) x It has advantages such as high conductivity, pseudocapacitive activity, two-dimensional layered structure, and abundant surface functional groups, making it an ideal electrode material that can provide efficient charge storage in electrochemical processes.
[0003] Wet spinning is the mainstream method for preparing MXene-based fiber electrodes, and the rheological properties of the spinning solution are the key to continuous molding. Pure MXene dispersions have insufficient viscosity at low concentrations and are prone to needle clogging at high concentrations, resulting in poor rheological properties and making stable continuous wet spinning impossible. MXene nanosheets exhibit strong π-π interactions and severe self-stacking, hindering ion transport and significantly reducing active sites. Pure MXene fibers have low mechanical strength and high brittleness, making it difficult to meet the requirements for wearable bending and weaving.
[0004] To address these issues, one approach is to introduce one-dimensional nanomaterials, such as cellulose nanofibers (CNFs), for physical modification. While CNFs can improve rheology and act as intercalating agents, their binding with MXene relies primarily on weak hydrogen bonds and physical entanglement, limiting their effectiveness. Another approach involves crosslinking from the hydrogel field, introducing polymers such as sodium alginate, and then performing a secondary crosslinking process using a solution containing divalent metal cations after fiber extrusion and solidification. However, this chemical crosslinking method has the following drawbacks: the process is cumbersome, increasing post-processing time and hindering continuous industrial production; the added metal cations can remain in large quantities within the fiber network, forming electrochemically inert substances that not only increase electrode dead mass but may also impede the rapid migration of electrolyte ions, leading to a reduction in specific capacity.
[0005] Therefore, without using the traditional secondary metal cation crosslinking step, in-situ internal network formation can be achieved in a single wet spinning step using the coagulation bath itself, realizing fiber integration and thus synergistically improving the overall performance of MXene fibers. However, how to design spinning solutions with such responsive characteristics and match them with specific coagulation bath systems remains unclear in the existing technology. Summary of the Invention
[0006] To address the shortcomings of MXene fiber modification technology, such as complex processes, residual metal ions, and difficulty in synergistic performance improvement, this invention provides a method for preparing MXene-based fibrous electrodes enhanced by CNF / SA dual rheological regulation and in-situ ionic crosslinking, achieving the goals of continuous spinnability, structural stability, high mechanical enhancement, and improved electrochemical properties.
[0007] To achieve the objectives of this invention, the adopted technical solution is as follows:
[0008] A method for preparing a CNF / SA dual rheology-controlled MXene-based fibrous electrode includes the following steps:
[0009] (1) Few-layered Ti3C2T x MXene preparation: Ti3AlC2 (MAX phase) powder was etched in situ using lithium fluoride (LiF) and concentrated hydrochloric acid to generate HF etching solution to obtain the etched phase. The etched phase was first ultrasonically exfoliated using an ultrasonic cell disruptor under ice-water bath conditions, followed by centrifugation, and the supernatant was collected to obtain a few-layer MXene aqueous dispersion.
[0010] The specific mass fraction of concentrated hydrochloric acid is 37%; the ratio of lithium fluoride (LiF) powder to concentrated hydrochloric acid is: 20~22.5 mL of concentrated hydrochloric acid is added for every 1 g of LiF powder;
[0011] The mass ratio of Ti3AlC2 to LiF was limited to 1:1 to 1:2. Concentrated hydrochloric acid was first allowed to react with LiF, followed by the addition of Ti3AlC2 (MAX phase) in small batches. The etching conditions were stirring at 40–45°C for 40–50 h. After etching, high-speed centrifugation was performed at 6000–9000 rpm for 10–20 min. An ultrasonic cell disruptor was used in an ice-water bath with an ultrasonic power of 300–500 W for 1–2 h. Low-speed centrifugation was performed at 3000–4000 rpm for 1–2 h.
[0012] (2) Preparation of MXene / CNF / SA composite spinning solution: First, weigh CNF and SA powders, add a small amount of water and mix them evenly, then slowly add them to the Mxene dispersion in step (1) and stir evenly. Filter and concentrate to obtain composite spinning solution.
[0013] Specifically, the mass percentage of CNF and SA in the Mxene dispersion is 5% to 15%; preferably 10%, with a CNF to SA mass ratio of 1:2 to 2:1. The mixture is then magnetically stirred until homogeneous and concentrated to a solid content of 30 to 50 mg / mL by filtration. -1 .
[0014] (3) Wet spinning and curing drying: The spinning solution is loaded into a syringe and squeezed into a chitosan-acetic acid coagulation bath through the needle under constant pressure. An in-situ complexation reaction occurs to form continuous gel fibers. The fibers are transferred to oil paper and dried at room temperature to obtain a flexible and continuous MCS (MXene / CNF / SA) composite fiber electrode.
[0015] Specifically, the pressure is 15~30 psi, the needle diameter is 800~900 µm, and the drying time is 20~24h.
[0016] The chitosan-acetic acid coagulation bath uses deionized water as the solvent, wherein the chitosan concentration is 0.33%~1.0% (w / v) and the acetic acid concentration is 0.67%~2.0% (v / v). The fibers are immersed in the coagulation bath at room temperature for 3~5 minutes.
[0017] More specifically, the coagulation bath consists of 100-150 ml of deionized water, 1-2 ml of acetic acid, and 0.5-1 g of chitosan. The fibers are soaked in the coagulation bath at room temperature for 3-5 minutes.
[0018] In this process, the composite spinning solution undergoes an in-situ interfacial ion complexation reaction with the positively charged chitosan in the coagulation bath and the negatively charged sodium alginate in the spinning solution at the moment of extrusion. While rapidly exchanging solvents and solidifying, a three-dimensional double cross-linked network is integrated between the MXene sheets to form continuous gel fibers.
[0019] (4) Assembly of fibrous supercapacitors: Using PVA / H2SO4 as gel electrolyte, two of the above composite fibers are assembled in parallel to prepare symmetrical micro supercapacitors.
[0020] Specifically, the gel electrolyte is prepared by adding polyvinyl alcohol (PVA) powder to deionized water, stirring slowly at 85-95 °C while slowly adding concentrated sulfuric acid, and stirring at room temperature for 1-2 h to obtain PVA / H2SO4 gel electrolyte.
[0021] The present invention also provides the application of the above-mentioned MXene / CNF / SA composite fiber electrode in flexible energy storage devices, especially fibrous supercapacitors.
[0022] Furthermore, symmetrical microfiber supercapacitors were assembled using PVA / H2SO4 as the gel electrolyte.
[0023] CNF and SA work synergistically to regulate rheology and intercalate, and as shown in the attached diagram, the interlayer spacing of MXene increases from 1.16 nm to 1.39–1.48 nm, suppressing layer self-stacking. The fibers are continuous and uniform, with a diameter of 160–180 μm and an oriented wrinkle and porous structure on the surface; the tensile strength is 25.5–174 MPa, and the fracture strain is 0.25%–1.5%; the interlayer spacing is 1.39–1.48 nm, the ion transport channels are continuously connected, the pseudocapacitive properties are significant, the ion transport is fast, and the hydrophilicity is good.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) This invention does not use the traditional method of adding metal ions for immersion crosslinking. Instead, it uses an acidic coagulation bath containing chitosan as a crosslinking agent. The amino group of chitosan and the carboxyl group of the spinning solution form an interfacial complex, which not only simplifies the preparation process, but also avoids interference from external metal ions, thus ensuring the purity and electrochemical properties of the fiber network.
[0026] (2) Single CNF physical reinforcement often has low strength. In this invention, CNF and chitosan-SA are ionically complexed and bonded in situ between MXene sheets. Under the synergistic effect, the composite fiber has high tensile strength and simultaneously meets the requirements of high strength and flexibility for weaving.
[0027] (3) Before spinning, SA and CNF work together to solve the shear thinning behavior of pure MXene, solve the needle blockage problem, and achieve continuous spinning. After forming, the in-situ crosslinking network effectively resists the shrinkage and self-stacking of MXene sheets in aqueous media and cyclic charging and discharging. The stable interlayer pore expansion effect exposes more pseudocapacitive active sites, so that the high-strength fiber not only does not reduce energy storage, but also achieves high specific capacity, while improving mechanical and electrochemical properties. Attached Figure Description
[0028] Figure 1 The rheological properties of the spinning solution are shown in the following figures: (a) viscosity versus shear rate; (b) storage modulus and loss modulus versus strain.
[0029] Figure 2 SEM images of the surface and cross-section of MCS (1:1) composite fibers; (a, b) surface SEM image; (c, d) cross-section SEM image.
[0030] Figure 3 (a) XRD patterns of three MCS composite fibers; (b) FTIR patterns of SA, MXene, and three MCS composite fibers;
[0031] Figure 4The tensile strength-strain curve of MCS composite fiber;
[0032] Figure 5 The (ac)CV and (df)GCD curves of the MCS supercapacitor are shown.
[0033] Figure 6 (a) EIS plot and (b) volumetric capacitance at different current densities for MCS supercapacitors.
[0034] Figure 7 (a) shows a comparison of the volumetric capacitance of supercapacitors made of composite fibers and single fibers; (b) shows a comparison of the tensile mechanical properties of composite fibers and single fibers. Detailed Implementation
[0035] This invention is not limited to the specific implementation methods listed below. Those skilled in the art can implement this invention using various other specific embodiments based on the content disclosed herein. Any modifications or alterations made to the design structure and concept of this invention fall within the protection scope of this invention. It should be noted that, unless otherwise specified, the embodiments and features described in this invention can be combined with each other.
[0036] Example 1: Preparation of MCS composite fiber electrode with CNF:SA = 1:2:
[0037] (1) 4 g of LiF powder was added to 80 mL of concentrated hydrochloric acid (mass fraction 37%), and magnetically stirred to dissolve it. The temperature was raised to 40℃, and 4 g of Ti3AlC2 (MAX phase) powder was added in batches. The mixture was stirred and etched at 40℃ and 390 rpm for 48 h. After the reaction was completed, the product was centrifuged at 8000 rpm for 10 min, and deionized water was added to wash repeatedly until the pH of the supernatant was ≈7. A small amount of deionized water was added, and the mixture was ultrasonically exfoliated using a 400 W cell disruptor in an ice water bath. Finally, the exfoliated suspension was centrifuged at 3500 rpm for 1 h, and the supernatant was collected to obtain a few-layer MXene solution with a concentration of about 13 mg / ml.
[0038] (2) Chitosan coagulation bath: Measure 100 mL of deionized water, add 1 mL of glacial acetic acid, and then add 0.5 g of chitosan powder (degree of deacetylation ≥95%, viscosity 100-200 mpa.s, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.). Stir continuously at room temperature until completely dissolved to obtain a colorless and transparent chitosan-acetic acid coagulation bath. Let it stand to remove bubbles for later use.
[0039] Wet spinning was performed to prepare the spinning solution. The specific method was as follows: CNF (200 nm in length, 4–10 nm in diameter, purchased from Shanghai Maclean Biochemical Technology Co., Ltd.) and SA (chemically pure, purchased from Sinopharm Chemical Reagent Co., Ltd.) were weighed according to a CNF / SA mass ratio of 1:2, with the total mass of CNF and SA being 10% of the mass of the active material in the Mxene dispersion. A small amount of deionized water was added to prepare a mixed solution, and the mixture was stirred for 30 min to achieve homogeneity. Then, while stirring, the CNF / SA mixed solution was slowly added dropwise to at least one layer of the Mxene dispersion, and stirring was continued for 4 h. The mixed solution was then concentrated to 40 mg / mL by vacuum filtration. -1 The composite spinning solution was obtained. The spinning solution was transferred to a syringe and extruded into a chitosan-acetic acid coagulation bath under a pressure of 20 psi through an 840 µm needle. The extruded gel fibers were soaked in the coagulation bath at room temperature for 5 min to crosslink and cure. They were then removed and transferred to oil paper and dried at room temperature for 24 h to obtain MCS (1:2) fiber electrodes.
[0040] (3) Assembling the supercapacitor. Two 2 cm long MCS composite electrodes were placed parallel to each other at a distance of 0.5 cm, with an overlap of 1 cm, and fixed to a PET film using double-sided tape. Then, a gel electrolyte was added to the overlapping area of the two electrodes, and copper foil was attached to the ends of the two composite fibers using silver paste and fixed with transparent tape for subsequent electrochemical testing. The gel electrolyte was prepared by adding 1 g of polyvinyl alcohol (PVA) powder to 10 ml of deionized water, stirring slowly at 90 °C, and simultaneously adding 2-3 g of concentrated sulfuric acid dropwise, stirring at room temperature for 1.5 h to obtain the PVA / H2SO4 gel electrolyte.
[0041] (4) Finally, electrochemical tests were performed on the assembled supercapacitor. The device was connected to an electrochemical workstation for electrochemical testing, with a voltage window of 0–0.8 V and a scan rate of 5–100 mV s. -1 .
[0042] Example 2: Preparation of MCS composite fiber electrode with CNF:SA = 1:1:
[0043] (1) First, few-layer Mxene was prepared. The specific method is the same as in Example 1.
[0044] (2) Next, prepare the spinning solution for wet spinning. The specific method is as follows: Weigh CNF and SA according to the following formula: the total mass of CNF and SA accounts for 10% of the mass of active material in the Mxene mixed solution, and the mass ratio of CNF to SA is 1:1. Add a small amount of deionized water to prepare a solution, mix and stir for 30 min, and then slowly add the mixed solution dropwise to the Mxene dispersion while stirring. Stir for 4 h to ensure that MXene and CNF are mixed evenly. Concentrate the mixed solution to 40 mg / mL by vacuum filtration. -1 The composite spinning solution was obtained. It was injected into the same chitosan-acetic acid coagulation bath as in Example 1 under a pressure of 20 psi through an 840 µm needle, soaked for 5 min, and dried at room temperature for 24 h to obtain MCS (1:1) fiber electrodes.
[0045] (3) Assemble the supercapacitor. The specific method is the same as in Example 1.
[0046] (4) Finally, the assembled supercapacitor is subjected to electrochemical testing. The specific method is the same as in Example 1.
[0047] Example 3: Preparation of MCS composite fiber electrode with CNF:SA = 2:1:
[0048] (1) First, few-layer MXene was prepared. The specific method is the same as in Example 1.
[0049] (2) Next, prepare the spinning solution for wet spinning. The specific method is as follows: the total mass of CNF and SA accounts for 10%, the ratio of CNF to SA is 2:1, mix and stir for 30 min, then slowly add the mixed solution dropwise to the Mxene dispersion while stirring for 4 h to ensure that MXene and CNF are mixed evenly. The mixed solution is concentrated to 40 mg / mL by vacuum filtration. -1 The composite spinning solution was obtained. It was injected into the same chitosan-acetic acid coagulation bath as in Example 1 under a pressure of 20 psi through an 840 µm needle, soaked for 5 min, and dried at room temperature for 24 h to obtain MCS (2:1) fiber electrodes.
[0050] (3) Assemble the supercapacitor. The specific method is the same as in Example 1.
[0051] (4) Finally, the assembled supercapacitor is subjected to electrochemical testing. The specific method is the same as in Example 1.
[0052] Comparative Example 1: Preparation of 10% M / S composite fiber electrode:
[0053] (1) 4 g LiF powder was added to 80 mL of concentrated hydrochloric acid (37%), and magnetically stirred to dissolve it. The temperature was raised to 40℃, and 4 g Ti3AlC2 (MAX phase) powder was added in batches. The mixture was stirred and etched at 40℃ and 390 rpm for 48 h. After the reaction was completed, the product was centrifuged at 8000 rpm for 10 min, and deionized water was added to wash repeatedly until the pH of the supernatant was ≈7. A small amount of deionized water was added, and the mixture was ultrasonically exfoliated using a 400 W cell disruptor in an ice-water bath. Finally, the exfoliated suspension was centrifuged at 3500 rpm for 1 h, and the supernatant was collected to obtain a few-layer MXene solution with a concentration of about 13 mg / ml.
[0054] (2) Preparation of spinning solution for wet spinning. The specific method is as follows: the mass of SA is 10% of the mass of active material in the Mxene mixed solution. The weighed SA powder is added to the Mxene dispersion in small batches, stirred for 4 h, and after being mixed evenly, the mixed solution is concentrated to 40 mg / mL by vacuum filtration. -1 The composite spinning solution was obtained. The spinning solution was transferred to a syringe and extruded into the same chitosan-acetic acid coagulation bath as in Example 1 through an 840 µm needle at a pressure of 20 psi. The solution was soaked at room temperature for 5 min and dried at room temperature for 24 h to obtain a 10% M / S fiber electrode.
[0055] (3) Assemble the supercapacitor. Place two 2 cm long M / S composite electrodes parallel to each other at a distance of 0.5 cm, with an overlap of 1 cm, and fix them to the PET film with double-sided tape. Then add gel electrolyte to the overlapping area of the two electrodes, and then use silver paste to attach copper foil to the ends of the two composite fibers and fix them with transparent tape for subsequent electrochemical testing.
[0056] (4) Finally, electrochemical tests were performed on the assembled supercapacitor. The device was connected to an electrochemical workstation for electrochemical testing, with a voltage window of 0–0.8 V and a scan rate of 5–100 mV s. -1 .
[0057] Comparative Example 2: Preparation of 10% M / C composite fiber electrode:
[0058] (1) First, few-layer MXene was prepared. The specific method was the same as that of Comparative Example 1.
[0059] (2) Preparation of spinning solution for wet spinning. The specific method is as follows: The mass of CNF is 10% of the mass of the active material in the Mxene mixed solution. The weighed CNF powder is added to the Mxene dispersion in small batches, stirred for 4 h, and after being mixed evenly, the mixed solution is concentrated to 40 mg / mL by vacuum filtration. -1The composite spinning solution was obtained. The spinning solution was transferred to a syringe and extruded into the same chitosan-acetic acid coagulation bath as in Example 1 through an 840 µm needle at a pressure of 20 psi. The solution was soaked at room temperature for 5 min and dried at room temperature for 24 h to obtain a 10% M / C fiber electrode.
[0060] (3) Assemble the supercapacitor. The specific method is the same as Comparative Example 1.
[0061] (4) Finally, electrochemical tests were performed on the assembled supercapacitor. The specific method was the same as that in Comparative Example 1.
[0062] Comparative Example 3: MCS composite fiber electrode with CNF:SA = 1:1 was prepared in a CaCl2 coagulation bath.
[0063] (1) First, prepare a few-layer MXene dispersion. The specific method is the same as that of Comparative Example 1.
[0064] (2) Calcium ion coagulation bath: Dissolve 5 g of anhydrous CaCl2 powder in 100 mL of deionized water to prepare a CaCl2 coagulation bath with a mass fraction of about 5%.
[0065] Wet spinning was performed to prepare the spinning solution. Specifically, the total mass of CNF and SA accounted for 10% of the active material mass of the Mxene mixed solution. A 1:1 mass ratio of CNF to SA was used, and a small amount of deionized water was added to prepare the solution. The mixture was stirred for 30 min, and then slowly added dropwise to the Mxene dispersion while stirring for 4 h to ensure homogeneous mixing of MXene and CNF. The mixed solution was then concentrated to 40 mg / mL by vacuum filtration. -1 A composite spinning solution was obtained. It was extruded into a CaCl2 coagulation bath under 20 psi pressure through an 840 µm needle. However, the extruded fibers were relatively hard, lacked plastic deformation, and under external force, they underwent brittle fracture, breaking into short cross-sectional fragments that could not be tested or analyzed.
[0066] To verify the synergistic effect of cellulose nanofibers (CNF) and sodium alginate (SA) in composite fibers, the fibers prepared in Example 2 were compared with those of Comparative Example 1 (without CNF) and Comparative Example 2 (without SA) in terms of mechanical and electrochemical properties. In terms of mechanical properties, the fiber strength of Comparative Example 1 was only 47.12 MPa, while the fiber strength of Comparative Example 2, lacking a cross-linked network, was 59.94 MPa. Example 2, relying on the cross-linked network structure jointly constructed by CNF and SA, achieved a fiber strength of 150.48 MPa, representing a significant improvement compared to the two comparative examples. Regarding electrochemical performance, at 0.5 A·cm⁻¹… -3 At the given current density, the volumetric specific capacity of Comparative Example 1 is 268.2 F·cm⁻¹. -3Comparative Example 2 is 344.68 F·cm -3 Example 2 is 327.5 F·cm -3 When the current density increases to 5 A·cm -3 At that time, the volumetric specific capacity of Comparative Example 1 decreased significantly to 86.875 F·cm⁻¹. -3 The rate capability decreased significantly, with Comparative Example 2 dropping to 185.94 F·cm⁻¹. -3 Example 2, however, still maintained a volumetric capacity of 201.88 F·cm⁻³, demonstrating superior rate stability. Overall, the results indicate that the synergistic blending of CNF and SA significantly enhances the mechanical properties of the fiber through the cross-linking network and optimizes the ion transport efficiency within the electrode, enabling the composite fiber to possess both excellent mechanical load-bearing capacity and electrochemical rate characteristics.
[0067] Figure 1 a represents the viscosity variation curves of spinning solutions prepared according to CNF and SA ratios of 1:2, 1:1, and 2:1, respectively, as a function of shear rate. All three spinning solutions exhibit shear-thinning behavior. At low shear rates, the viscosity decreases sharply with increasing shear rate, while at high shear rates, the viscosity tends to stabilize, approaching the Newtonian fluid plateau, which meets the requirements of wet spinning for spinning solutions. Figure 1 b is the curve of the corresponding modulus as a function of strain. As the strain increases, the curves of storage modulus and loss modulus intersect, indicating that the spinning solution changes from a solid-like state to a liquid-like state.
[0068] Figure 2 The MCS (1:1) fiber samples exhibited a morphology similar to that of M / C composite fibers. The addition of SA further enhanced the interlayer forces of MXene, leading to more severe shrinkage of the MCS fibers after drying, deepening surface wrinkles and grooves, and exposing more active sites on the fiber surface. The diameter of the dried fibers was approximately 160–180 μm.
[0069] Figure 3 The XRD patterns of MCS composite fibers with different ratios are shown. Compared to pure MXene, the interlayer spacing d value corresponding to the (002) characteristic peak of pure MXene is 1.16 nm. The interlayer spacing of all three groups of samples increased, proving that CNF-SA successfully intercalated and inhibited the self-stacking of MXene nanosheets; the interlayer spacing of MCS (1:1) was smaller than that of the other two groups due to the formation of a dense double network by the cross-linking of the three components. FT-IR was used to characterize SA, pure MXene, and the three groups of MCS fibers ( Figure 3 b) Verify strong interfacial interactions: 3200~3500 cm -1 The broad absorption peak is due to the OH stretching vibration of MXene; 2849 cm⁻¹ -1The characteristic peak is attributed to the -CH2 group of SA, and the peak intensity increases with the increase of SA content.
[0070] Figure 4 The mechanical properties of MCS composite fibers with different ratios are shown. It can be seen that MCS (1:1) balances strength and toughness, making it more suitable as a matrix material for flexible microelectrodes, and providing a stable mechanical basis for subsequent electrochemical performance testing. Figure 4 (b) Tensile mechanical properties of MCS composite fibers with different ratios. The results show that the 1:1 ratio of MCS composite fibers can achieve a synergistic improvement in strength and toughness, and has the best overall mechanical properties.
[0071] Figure 5 AC refers to three ratios of MCS composite fiber electrodes in the range of 0.5~5 A·cm. -3 The GCD curve below, Figure 5 df is 5~100 mV·s -1 The CV curves of the three groups of samples showed high symmetry and low voltage drop, indicating excellent charge-discharge reversibility and rate performance. The CV curves were generally rectangular, with a weak redox peak at 0-0.3 V, corresponding to the MXene intercalation pseudocapacitive reaction. The energy storage mechanism was a combination of double layer and pseudocapacitance. Furthermore, the curves did not show significant distortion after the scan rate increased, indicating good ion kinetics performance.
[0072] Figure 6 Figure 6b shows the EIS curves of the three composite electrodes. The slope of the curve for the MCS (1:1) fiber electrode is the steepest in the low-frequency range, indicating that its ions diffuse the fastest within it. This is due to its densest cross-linked network and well-ordered ion transport channels. The volumetric capacitance of the corresponding supercapacitors was calculated based on the GCD curves. The supercapacitor made with the MCS (1:1) fiber electrode has the best electrochemical performance (Figure 6b).
[0073] Figure 7 (a) Comparison of volumetric capacitance between composite fiber and single fiber supercapacitors; Figure 7 (b) Comparison of tensile mechanical properties between composite fibers and single fibers; MCS composites achieve simultaneous improvement in strength and toughness compared to pure MS and pure MC.
[0074] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a CNF / SA dual rheological control and in-situ ionic crosslinking enhanced MXene-based fibrous electrode, characterized in that, Including the following steps: (1) Few-layered Ti3C2T x MXene preparation: Ti3AlC2 was etched with HF etching solution, followed by centrifugal cleaning, ultrasonic peeling, and low-speed centrifugation to obtain a few-layer MXene aqueous dispersion; (2) Preparation of MXene / CNF / SA composite spinning solution: Aqueous dispersion containing cellulose nanofibers (CNF) and sodium alginate (SA) is mixed evenly, and then added dropwise to at least one layer of MXene dispersion and stirred. After thorough mixing, the mixture is concentrated by vacuum filtration to obtain MXene / CNF / SA composite spinning solution; wherein the total mass of CNF and SA accounts for 5% to 15% of the mass of MXene, and the mass ratio of CNF:SA is 1:2 to 2:1; (3) The composite spinning solution is extruded into a coagulation bath containing chitosan-acetic acid for wet spinning and forming, solidification in situ and ion crosslinking to obtain composite gel fiber; (4) Take out the composite gel fiber and dry it at room temperature to obtain the MXene / CNF / SA composite fiber electrode.
2. The method for preparing CNF / SA dual rheological regulation and in-situ ionic crosslinking enhanced MXene-based fibrous electrode according to claim 1, characterized in that, Step (1) specifically involves: generating an HF etching solution in situ using lithium fluoride and concentrated hydrochloric acid, adding Ti3AlC2 powder to it in portions at 40~45℃ and stirring continuously for 40~50 h; After etching, the high-speed centrifugation conditions were 6000~9000 rpm for 10~20 min; ultrasonic cell disruptors were used to process the cells in an ice-water bath environment, with the ultrasonic power set to 300~500 W and the ultrasonic time set to 1~2 h for ultrasonic exfoliation. Finally, the supernatant was collected by centrifugation at 3000~4000 rpm for 1~2 h to obtain a few-layer MXene aqueous dispersion.
3. The method for preparing CNF / SA dual rheological regulation and in-situ ionic crosslinking enhanced MXene-based fibrous electrode according to claim 1, characterized in that, In step (2), the total mass of the cellulose nanofibers and sodium alginate accounts for 10% of the mass of MXene.
4. The method for preparing CNF / SA dual rheological regulation and in-situ ionic crosslinking enhanced MXene-based fibrous electrode according to claim 1, characterized in that, In step (2), the solid content of the MXene / CNF / SA composite spinning solution is 30~50 mg·mL. -1 .
5. The method for preparing CNF / SA dual rheological regulation and in-situ ionic crosslinking enhanced MXene-based fibrous electrode according to claim 1, characterized in that, In step (3), the constant pressure of spinning extrusion is 15~30 psi, and the inner diameter of the extrusion needle is 800~900 μm; the cationic coagulation bath uses deionized water as solvent, wherein the mass volume concentration of chitosan is 0.33%~1.0%, and the volume concentration of glacial acetic acid is 0.67%~2.0%.
6. In the method for preparing CNF / SA dual rheological regulation and in-situ ionic crosslinking enhanced MXene-based fibrous electrode according to claim 1, in step (3), after the composite spinning solution is extruded into a cationic coagulation bath, the resulting fiber continuum is soaked in the coagulation bath at room temperature for 3-5 min to complete the crosslinking and curing.
7. An MXene / CNF / SA composite fiber electrode prepared by the method according to any one of claims 1-6.
8. The application of the fibrous electrode according to claim 7 in a fibrous supercapacitor, characterized in that: A symmetrical micro supercapacitor was assembled using PVA / H₂SO₄ as the gel electrolyte, with an operating voltage of 0–0.8 V and a capacity of 0.5 A·cm⁻¹. -3 The specific volumetric capacity reaches 327.5 F·cm³. -3 .